2021
DOI: 10.3390/su13084491
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Extracts from Caulerpa lentillifera Waste: An Alternative Product in a Circular Economy

Abstract: Nowadays, a circular economy is one of the main strategies for developing a sustainable economy. The objective of this work was to increase the value of Caulerpa lentillifera waste and use it efficiently as a resource for lipid extraction. A crude lipid yield of approximately 27.69% of the dry weight was obtained under the following optimized conditions that consisted of a three-stage extraction with 15 min/stage using a ratio of 1:10 (w/v) at room temperature. The crude extracts contained a total fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The 2930 and 2830 cm −1 represented the absorption peaks of methylene groups of fatty acids. It was indicated that the CL extract contained 45% palmitic acid (Srinorasing et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2930 and 2830 cm −1 represented the absorption peaks of methylene groups of fatty acids. It was indicated that the CL extract contained 45% palmitic acid (Srinorasing et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It was attributed to the presence of phenolics, and flavonoids contained in CL extract within composite films. It was found that the CL extract contained total phenolic and flavonoid contents around 2.07 mg GAE per g sample and 5.40 mg QE per g sample, and monounsaturated fatty acids accounted for 9.5% of the total extract (Srinorasing et al ., 2021). Fatty acids within composite films affected the swelling rate of films, which affected the release of active agent (Dai et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional value was reported to be not different from that of food-grade products (Chaiklahan et al 2020). The studies focused on the polysaccharide (Chaiklahan et al 2020;Honwichit et al 2022), as well as the lipid (Srinorasing et al 2021) fraction. In intra-species comparisons (Table 2) different extraction methods, namely varying algae-to-ethanol ratios, extraction times, stages and purifications were tested to obtain the highest yield of the respective target metabolites (Chaiklahan et al 2020;Srinorasing et al 2021).…”
Section: Nutritional Valuementioning
confidence: 99%
“…The studies focused on the polysaccharide (Chaiklahan et al 2020;Honwichit et al 2022), as well as the lipid (Srinorasing et al 2021) fraction. In intra-species comparisons (Table 2) different extraction methods, namely varying algae-to-ethanol ratios, extraction times, stages and purifications were tested to obtain the highest yield of the respective target metabolites (Chaiklahan et al 2020;Srinorasing et al 2021). Regarding polysaccharide extraction, two-stage extraction with 60 min/stage, a solid-to-liquid ratio of 1:15 (w/v), extraction temperature of 90 °C, and two time precipitation by a concentration of 75% ethanol was reported to obtain highest polysaccharide yields of around 25% of DW (Chaiklahan et al 2020) and the hot water extraction (pH 6, 90 °C for 20 min) was the most cost-effective (Honwichit et al 2022).…”
Section: Nutritional Valuementioning
confidence: 99%